Bob Flanagan, quand les performances d’un supermasochist exorcisent la mort (Altre Modernità, 2010)
Since the end of the last century, we’ve noticed in our western society an uneasiness regarding the mention of death. Whereas some mystical dimension allowed man to give death a meaning, the Hegelian-Nietzschean prophecy of the death of God made this impossible. Indeed, knowing that the promise of a Kingdom of Heaven was not assured any more, man prefered to obscure the death that haunted him. Despite the difficulty to face this ontological condition, we can see that the subject of death is more and more present on the contemporary artistic scene. The body which is central in relation to this problematic becomes for the artist the material through which death exorcizes and declines itself. However, from Body Art achievements to the exhibition of corpses, we can see that the experiment of death only seems possible through the treatment of the body as a martyr. If Body Art protagonists seem to find in it their model to experiment the human being in the limits of their own bodies and thus comprehend death, there are others for whom it’s the diagnosed death that is shaping the relationship to their own bodies. That’s the case with Bob Flanagan. Doomed since childhood by cystic fibrosis, we will see how this artist, by the detour of borderline achievements with a masochistic tendency and ritualised on a setting of Christianity, will redefine his relationship to the body experience and through this manage to exorcize the idea of an impending death.